Detection of Class 1 integron-intI1 Associated with Neomycin and Ciprofloxacin Resistant Bacteriain Different Spots of Bay Receiving Sewage water (Medico Legal Update, 2020)
In this study, Class 1 Integron co associated with some antibiotics resistant bacteria was investigated fromdifferent spots on Izmir bay of Aegean sea as a first report about analysis and track of influences human andanimal wastes on water environment in a period between July 2019 – January 2020.Our results showed variations in Neomycin and Ciprofloxacin resistance bacteria, Neomycin resistancebacteria was detected in100 % of all sampling points ranged from 4.2×102 in (BOS) samples to 1.98×10revealing wide distribution of Neomycin resistance bacteria in different spots on Izmir bay receiving sewagewater.Ciprofloxacin resistance bacteria founded in 25 % of collected samples it was only founded in (BS) samplingpoint, Class 1 integron investigation, showed wide range distribution during sampling campaign amongdifferent sampling points, the main results showed that 75 % of samples was positive to class 1 integronpresence, it was founded in Balçova Ilica (BS), Melez (MS), Bornova (BOS) points with no appear in thefourth point Bostanli streams (BTS).During the investigations we noticed that Class 1 integron elements was associated 100 % with Neomycinresistance bacteria in four sampling points (BS, MS, BOS & BTS) while showed weak association withCiprofloxacin resistant bacteria.